Pengaruh Penggunaan E-Learning Sebagai Media Pelatihan Terhadap Kinerja Peserta Pelatihan di Balai Diklat KKB Jember - Jessica Rahel Dethan (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
The era of industrial revolution 4.0 and 5.0 has driven technological transformation across various sectors, including education and training. Nowdays, individuals face increasing demands in the workplace with complex tasks and responsibilities. Busy work schedules, high mobility, and pressure to archive targets often become challenges for personal development. To address these challenges, The National family planning and population training center in jember has adopted e-learning to improve the performance of training participants, including family planning instructors, particularly those newly appointed as civil servants. This study was conducted to determine the effect of using e-learning as a training medium on the performance of training participants The research employed a quantitative method involving 68 respondents who were participants of the civil servants training batch 21-24 in the year 2024. The data analysis methods use simple linear regression analysis. The result of the simple linear regression analysis produced the equation Y = 14,647 + 1,287X. The positive regression coefficient of 1,287 indicates that the e-learning variable (X) has a positive effect on the performance variable (Y). The study also found that the use of e-learning has a positive and significant effect on the performance of training participants. This is evidenced by the t-test significance value of 0,000, which is less than 0,05, and a coefficient of determination (R²) of 0,795 or 79,5%, E-learning infrastructure was identified as the most dominant factor, contributing significantly to training effectiveness. In conclusion, e-learning not only serves as a practical solution for remote training but also plays a crucial role in shaping superior and competitive performance in line with the demands of professionalism from family planning instructors in the digital era.
Reupload File Repository 17 Juni 2026_Yudi Approved by Teddy
Keywords: E-learning; training media; performance